KEMAMPUAN MEMBACA PEMAHAMAN CERITA PENDEK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA SISWA MADRASAH IBTIDAIYAH - Yuliwati Yuliwati (Universitas PGRI Palembang, 2017)
Background in this research is learning comprehension reading never increase because using conventional method. The formulation of the problem in this research is 1) How is the model of cooperative learning model Student Team Achievement Division (STAD) can improve students ability in reading comprehension of short story?; and 2) How is the result of improving students ability in reading comprehension of short story by using STAD type cooperative learning model ?. The research method used is Classroom Action Research (PTK). Technique of collecting data in this research use Observation and test. The conclusion of the research result shows that the application of Cooperative STAD type learning model can improve reading comprehension ability in the students of Grade V of Madrasah Ibtidaiyah Hijriyah 6 Palembang. In cycle 1 only 4 people (13.33%) of the students who complete the value of KKM 75, and the remaining 26 people (86.67%) did not reach KKM 75. In cycle II showed that 18 people (60.00%) students who (KKM 75) did not reach KKM 75. In the third cycle, the students who complete the KKM 75 score of 29 (96.67) and the rest only 1 person (3.33 %) did not reach KKM 75. This means that the achievement rate of learning achievement of 85% is categorized as successful and does not need further action of the next cycle. Keywords: reading comprehension, STAD type cooperative learning model, short story